Double‐Chamber Microbial Fuel Cell with a Non‐Platinum‐Group Metal Fe–N–C Cathode Catalyst. Issue 5 (21st January 2015) - Santoro, Carlo; Serov, Alexey; Narvaez Villarrubia, Claudia W.; Stariha, Sarah; Babanova, Sofia; Schuler, Andrew J.; Artyushkova, Kateryna; Atanassov, Plamen
Abstract Non‐Pt‐group metal (non‐PGM) materials based on transition metal–nitrogen–carbon (M–N–C) and derived from iron salt and aminoantipyrine (Fe‐AAPyr) of mebendazole (Fe‐MBZ) were studied for the first time as cathode catalysts in double‐chamber microbial fuel cells (DCMFCs). The pH value of the cathode chamber was varied from 6 to 11 to elucidate the activity of those catalysts in acidic to basic conditions. The Fe‐AAPyr‐ and Fe‐MBZ‐based cathodes were compared to a Pt‐based cathode used as a baseline. Pt cathodes performed better at pH 6–7.5 and had similar performances at pH 9 and a substantially lower performance at pH 11 at which Fe‐AAPyr and Fe‐MBZ demonstrated their best electrocatalytic activity. The power density achieved with Pt constantly decreased from 94–99 μW cm−2 at pH 6 to 55–57 μW cm−2 at pH 11. In contrast, the power densities of DCMFs using Fe‐AAPyr and Fe‐MBZ were 61–68 μW cm−2 at pH 6, decreased to 51–58 μW cm−2 at pH 7.5, increased to 65–75 μW cm−2 at pH 9, and the highest power density was achieved at pH 11 (68–80 μW cm−2). Non‐PGM cathode catalysts can be manufactured at the fraction of the cost of the Pt‐based ones. The higher performance and lower cost indicates that non‐PGM catalysts may be a viable materials choice in large‐scale microbial fuel cells.